Ethnoveterinary botanical survey of medicinal plants used in Pashto, Punjabi and Saraiki communities of Southwest Pakistan. Issue 5 (22nd July 2021) - Abidin, Sheikh Zain Ul; Munem, Afifa; Khan, Raees; Batiha, Gaber El‐Saber; Amhad, Mushtaq; Zafar, Muhammad; Khalil, Atif Ali Khan; Hetta, Helal F.; Mahmoud, Mohamed H.; Sami, Abdus; Bhatti, Muhammad Zeeshan
Abstract: Medicinal plants are highly used in the ethnoveterinary practice as considerable livestock resources in remote areas. The aim of the present study is to explore the ethnoveterinary medicinal practices in three different communities and discuss the cross‐cultural consensus on the usage of medicinal plants for the treatment of animals. The field survey was conducted by the animal healers of the area during the different seasons of plant growth. A total of 83 informants were interviewed through Semi‐structured interview involving experts of traditional knowledge in 21 localities of the three regions (Zhob, D. I. Khan and Mianwali) were conducted. Findings of the study were quantitatively analyzed through the informant consensus factors to identify the homogeneity information provided by the informants. Furthermore, cross‐culture consensuses were analyzed and recorded data were represented in a tabulated and Venn diagrams. In particularly, 59 species of plants were documented in the comparative analysis. Among them, 32 plant species were recorded in Pashto community, while Punjabi and Sarakai communities exhibited nine and four plant species, respectively. Whereas cross‐cultural analysis showed 14 medicinal plants that were commonly utilized by three different ethnic communities, that indicated low interregional consensus in regard to ethnoveterinary practices of medicinal plants. The current study showed that different communities and ethnic groups sharing some traditional knowledge and cross‐culturally approaches have been reported from traditional uses of plants against livestock's diseases. Therefore, current findings are the opportunities to scrutinize the plants for the discovery of new drug sources for humans and animals. Abstract : This research work provides the cross‐cultural information about medicinal plants in different communities of three different regions in the Southwest Pakistan. Cross‐cultural analysis showed medicinal plants was commonly used among three ethnic communities that indicates a low interregional consensus with regard to the ethnoveterinary practices of medicinal plants.